KEDUDUKAN HAKIM TUNGGAL DALAM GUGATAN SEDERHANA (SMALL CLAIM COURT) - Ferevaldy, Adisti Pratama; Anand, ghansham (Departemen Hukum Perdata, 2017)
The Civil Procedure has several principles in its application. One of them is the principle of simple, efficient and low cost trial. The simple principle of organizing the trial is done by a simple and definite mechanism. The efficient principle means that trials are held within an appropriate deadline. The principle of low cost means the cost of the trial is payable. The cost shall be determined by considering the amount of reasonable cost and can be reached by various circles of Indonesian society. In the case of supporting the creation of a efficient, simple and low cost trial principle, the Supreme Court issued the Supreme Court Regulation Number 2 Year 2015 on the Procedures of Small Claim Court. The Regulation of the Supreme Court is one of the forms of the existing law in Law of the Republic of Indonesia Number 12, Year 2011 concerning the Establishment of Laws and Regulations. However, the regulation posseses a problem that is contrary to Law of the Republic of Indonesia Number 48, Year 2009 concerning Judicial Power. The problem is the use of a single judge which is not in accordance with the provisions contained in the Law concerning Judicial Power which mentioned that the judges of a trial should at least consist of 3 people. The position of a single judge in the small claim court is intended to make the trial process faster and more efficient which in this case presents that the judiciary in Indonesia embraces the principle of speedy, simple and low cost. The Supreme Court Regulation shall not be contrary to existing laws.